Analisis efisiensi industri perbankan Indonesia setelah merger dan akuisisi: Pendekatan data envelopment analysis - Sipangkar, Yoshua Harbyanto; Sihaloho, Estro Dariatno (Jurnal Manajemen Maranatha, 2020)
This article determines the factor that influences bank efficiency after mergers and acquisitions. The efficiency calculation uses Data Envelopment Analysis (DEA) approach. To test the factors, we use cross-section method in the first three years after mergers and acquisitions. The studies are analyzing the impact of identical factors with bank characteristics such as governance, credit risk, capital adequacy, and loan intensity on bank efficiency, herewith total assets as a control variable. The result shows that governance and credit risk have no significant effect on bank efficiency after mergers and acquisitions. Capital adequacy has a positive and significant effect on bank efficiency in the first three years after mergers and acquisitions. Loan intensity has a positive and significant effect on bank efficiency in the second and third years.